Evolutionary transitions in broad tapeworms (Cestoda: Diphyllobothriidea) revealed by mitogenome and nuclear ribosomal operon phylogenetics - Fraija-Fernández, Natalia; Waeschenbach, Andrea; Briscoe, Andrew G; Hocking, Suzanne; Kuchta, Roman; Nyman, Tommi; Littlewood, D Timothy J (Molecular phylogenetics and evolution, 2021)
Broad tapeworms (Diphyllobothriidea) are parasites whose adults are capable of infecting a wide range of freshwater, marine and terrestrial tetrapods including humans. Previous works examining the evolution of habitat and host use in this group have been hampered by the lack of a well-resolved phylogeny. In order to produce a robust phylogenetic framework for diphyllobothriideans, we sequenced the complete mitochondrial genome of 13 representatives, carefully chosen to cover the major clades, and two outgroup species representing the Spathebothriidea and Haplobothriidea. In addition, complementary data from the nuclear ribosomal operon was sequenced for 10 representative taxa. Mitogenomes and ssrDNA and lsrDNA were used towards elucidating the phylogenetic framework for the Diphyllobothriidea. The Cephalochlamydidae is confirmed as the earliest diverging diphyllobothriidean lineage, and Solenophoridae and Diphyllobothriidae are sister groups. We infer a probable freshwater origin of the diphyllobothriideans. The ancestral condition for life cycle complexity could not be unambiguously resolved. However, we infer exclusive use of a three-host life cycle following the origin of the Solenophoridae + Diphyllobothriidae. Regarding definitive host use, although we infer reptiles as the most likely ancestral condition, this result should be revisited with a more densely sampled phylogeny in future studies. Freshwater habitat is used by the early diverging lineages within the Solenophoridae + Diphyllobothriidae clade. For the latter, habitat use shifts between freshwater and marine environments, and definitive host use includes marine and terrestrial mammals and birds. We use mitochondrial genomes to distinguish Schistocephalus species occurring in different species of sticklebacks and demonstrate conspecificity of Ligula cf. intestinalis specimens collected from two Fennoscandian ringed seal subspecies.
Keywords: Cestoda; Phylogeny; operon; genom mitochondriální; Genome, Mitochondrial; Animals; 18S rDNA; lidé; 28S rDNA; Ancestral character estimation; Diphyllobothriosis; Genome-skimming; Sparganosis; Systematics; Humans; zvířata; fylogeneze; Operon